Assessments of Acoustical Performance of Classrooms and Teachers’ Acoustical Comfort in The School Environment – A Case Study - Tong, Y. G.; Md Amin, N. D.; Othman, M. H.; Abas, N. H.; Ewon, U; Mohd Zaim, M. A. Z; Dass, D. A. Robert (International Journal of Integrated Engineering, 2022)
Acoustic comfort in classroom is significant to protect the health and enhance scholastics performance of both students and teachers. The aim of this study is to evaluate the acoustic comfort in a primary school of SK Bukit Soga, Batu Pahat through objective and subjective evaluations. Field measurements were carried out to measure the background noise and reverberation time inside the classrooms. Six classrooms were tested to investigate the acoustic performance of the learning spaces of this school. Besides, questionnaires survey and interviews have also been conducted to assess the acoustic comfort of the teachers on the teaching and learning process. The measured background noise and reverberation times inside all the selected classrooms were very high comparing to the recommended values. The results from the survey showed that teachers were not satisfied with the acoustics comfort of this school’s acoustic environment.